2019
DOI: 10.1017/s0950268819000475
|View full text |Cite
|
Sign up to set email alerts
|

A One Health investigation of Salmonella enterica serovar Wangata in north-eastern New South Wales, Australia, 2016–2017

Abstract: Salmonella enterica serovar Wangata (S. Wangata) is an important cause of endemic salmonellosis in Australia, with human infections occurring from undefined sources. This investigation sought to examine possible environmental and zoonotic sources for human infections with S. Wangata in north-eastern New South Wales (NSW), Australia. The investigation adopted a One Health approach and was comprised of three complimentary components: a case–control study examining human risk factors; environmental and animal sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 28 publications
(35 reference statements)
2
27
0
Order By: Relevance
“…An additional 4 S. Wangata isolates were obtained from wildlife scats collected in parallel to the outbreak investigation. The epidemiological findings from this investigation have been reported in detail elsewhere [9]. These showed that indirect contact with bats/flying foxes, wild frogs and wild birds were statistically associated with human illness.…”
Section: Introductionsupporting
confidence: 70%
See 4 more Smart Citations
“…An additional 4 S. Wangata isolates were obtained from wildlife scats collected in parallel to the outbreak investigation. The epidemiological findings from this investigation have been reported in detail elsewhere [9]. These showed that indirect contact with bats/flying foxes, wild frogs and wild birds were statistically associated with human illness.…”
Section: Introductionsupporting
confidence: 70%
“…Ninety Australian S. Wangata isolates were included in this study, 84 of which were obtained during an outbreak investigation conducted between November 2016 and April 2017 [9]. An additional six isolates were included and were obtained from routine surveillance of food (n = 3) and humans (n = 3) in NSW.…”
Section: S Wangata Isolatesmentioning
confidence: 99%
See 3 more Smart Citations